Penyuluhan Tentang Penularan Dan Pencegahan Scabies Di Lembaga Pemasyarakatan Klas IIB Kota Padangsidimpuan - Sri Sartika Sari Dewi; Yulinda Aswan (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2020)
The Community Partnership Program implemented in this manuscript is a baby massage training for Kader Posyandu of Toddler. Massage in the baby will stimulate the vagus nerve. This nerve will increase intestinal peristalsis, so that emptying of the stomach faster will thus stimulate the baby's appetite to eat more in an adequate amount. On the other hand baby massage can also improve blood circulation and increase cell metabolism, so that the baby's weight will increase. Partners in the implementation of this PKM are posyandu cadres under five at the Labuhan Rasoki Puskesmas. The problems found are the low coverage of exclusive breastfeeding to infants and the growth of infant development is not optimal, marked by body weight that is not age-appropriate. The PKM implementation begins with coordination with the KIA officer to contact the cadre leader and members who will be the participants of the activity. This activity was held 3 times. Participants in this activity totaled 35 people. In the first meeting questionnaires were distributed to see the cadres' knowledge, health education activities were carried out about infant massage, then questionnaires were distributed again. At the second meeting baby massage training was held. At the third meeting, baby massage assistance was carried out. During the implementation of the activity the participants were always enthusiastic and enthusiastic in participating in the series of activities. After completing the PKM implementation, the Kader Posyandu of toddlers was able to carry out baby massage.